HUBUNGAN ANTARA AKTIVITAS PENGUNJUNG DENGAN KONDISI TAMAN UMUM DI KECAMATAN BANDUNG WETAN - Framesthi, Dyah Bayu; Hindersah, Hilwati (Program Studi Perencanaan Wilayah Kota, 2010)
There is an emerging problem related to the declining quality of the urban environment, particularly in the availability of green open space which is one of the interesting issues, because the green open spaces have a very important role for the ecological sustainability. Green open space is often overlooked by the urban citizen who are less concerned about the role and functions. Public parks as a form of green open space available in Kecamatan Bandung Wetan mostly a park with manicured condition but some of them are not well maintained garden with a condition which poorly maintained, dirty (lots of junk), less green (the number of plants is reduced, because the dead or due to damage), damage and availability of facilities in the park. This research wanted to question as to whether there is a relation between the activity of visitors to the condition of a public park in Kecamatan Bandung Wetan. It aims to identify whether there is any relation between the activities of visitors to the condition of a public park in Kecamatan Bandung Wetan in the present. This research uses crosstabs analysis - Chi Square with a variable number of visitors by gender (male and female visitors) and common garden conditions (completeness of facilities, type of activity, concern for the condition of public parks as well as the visual impression visitors to see a public park).